Effect of volume concentration and sonication time on the performance of a hybrid solar collector based hydrogen production system with hybrid nanofluid: An experimental investigation - Hariharan Ramesh; S. Senthil Raja; R. Gangadevi; M. Baskaran; R. Marimuthu (Case Studies in Thermal Engineering)
In the last few years, hydrogen has gained prominence as a viable alternative fuel to satisfy energy requirements and reduce the harmful emissions linked to fossil fuels. While several approaches such as steam methane reforming, coal gasification, electrochemical methods, and thermochemical methods may be used for hydrogen generation, there has been a growing interest among scientists in solar energy-based hydrogen production over the last years. This paper presents the design, construction, and experimental evaluation of an independent device using a PVT solar collector for the generation of environmentally friendly hydrogen using various nanofluids. The impact of the volume ratio and sonication duration of nanofluid on the efficiency of the PVT-based hydrogen generation system is analyzed. At a volume concentration of 0.2 % and sonication duration of 4 h for Alumina/water, CuO/water, and hybrid nanofluid in a PVT system, the electrical efficiencies recorded were 6.92 %, 7.73 %, and 8.34 %, respectively. This approach using a 0.2 % Alumina – CuO/water nanofluid with a sonication time of 4 h achieved an electrical efficiency of 8.34 % and a hydrogen production rate of 29.6 ml/min. Consequently, the hybrid nanofluid-cooled PVT-based hydrogen production system is more efficient and has significant potential for producing hydrogen without polluting the surroundings.